2006
DOI: 10.1016/j.taap.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenocystine on lead-exposed Chinese hamster ovary (CHO) and PC-12 cells

Abstract: Lead is a pervasive environmental toxin that affects multiple organ systems, including the nervous, renal, reproductive, and hematological systems. Even though it is probably the most studied toxic metal, some of the symptoms of lead toxicity still cannot be explained by known molecular mechanisms. Therefore, lead-induced oxidative stress has recently started to gain attention. This in vitro study confirms the existence of oxidative stress due to lead exposure. Administration of lead acetate (PbA) to cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Some clinical studies confirm the activation of antioxidants as a result of lead action [13,20]. Also, in vitro administration of lead acetate (500 μmol/l) to cell cultures showed an increase of both MDA concentration and antioxidant enzymes activity (GPx, CAT) [21]. On the other hand, the incubation of erythrocytes in the presence of lead (5 μmol/l) inhibited the activity of GPx, SOD, and catalase [22].…”
Section: Discussionmentioning
confidence: 87%
“…Some clinical studies confirm the activation of antioxidants as a result of lead action [13,20]. Also, in vitro administration of lead acetate (500 μmol/l) to cell cultures showed an increase of both MDA concentration and antioxidant enzymes activity (GPx, CAT) [21]. On the other hand, the incubation of erythrocytes in the presence of lead (5 μmol/l) inhibited the activity of GPx, SOD, and catalase [22].…”
Section: Discussionmentioning
confidence: 87%
“…We showed that the protective mechanism of Selol against SNP cytotoxicity included significant inhibition of ROS production along with the restoration of GSH homeostasis, and the expression/activity of antioxidative enzymes. Similarly, Aykin-Burns et al showed that selenocystine (SeCys) also ameliorated lead-induced imbalance of the GSH/GSSG ratio [55]. In addition, pretreatment with SeMet for 16 h has been shown to protect primary rat hippocampal neurons against the toxicity of ROS generated by iron/hydrogen peroxide (Fe 2+ /H 2 O 2 ) or amyloid β.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the medium composition has to be considered when supplementing cultures with selenium as this compound can interact with other trace elements. Finally, selenocysteine supplementation has also been demonstrated to decrease cell death of CHO cells exposed to lead‐induced oxidative stress (Aykin‐Burns & Ercal, ).…”
Section: Medium Development Approaches To Limit Oxidative Stressmentioning
confidence: 99%
“…Finally, selenocysteine supplementation has also been demonstrated to decrease cell death of CHO cells exposed to lead-induced oxidative stress (Aykin-Burns & Ercal, 2006).…”
Section: Trace Elements and Chelatorsmentioning
confidence: 99%